Ductile fracture prediction in metal forming processes - Vaz M.* (2008)
Numerical prediction of ductile failure in metal forming processes under generic deformation paths has been a challenge to researchers. Ductile fracture indicators for tensile-dominant problems have been described in the literature since early nineties; however, compressive-dominant forming operations yield different failure mechanisms, which cause most of the classical indicators to fail. This work describes a modelling strategy based on damage concepts which accounts for both void opening (tension) and void closure (compression) effects. The numerical results are validated against experimental results for compression tests and tensile tests of notched specimens. © 2008 Inderscience Enterprises Ltd.